A comparison of treatment response to biologics in asthma-COPD overlap and pure asthma: Findings from the PRISM study - Ji-Su Shim, MD, PhD; Hyunkyoung Kim, MS; Jae-Woo Kwon, MD, PhD; So-Young Park, MD, PhD; Sujeong Kim, MD, PhD; Byung-Keun Kim, MD, PhD; Young-Hee Nam, MD, PhD; Min-Suk Yang, MD, PhD; Mi-Yeong Kim, MD, PhD; Sae-Hoon Kim, MD, PhD; Byung-Jae Lee, MD, PhD; Taehoon Lee, MD, PhD; et al. (World Allergy Organization Journal, 2023)
Background: Despite the increasing use of biologics in severe asthma, there is limited research on their use in asthma-chronic obstructive pulmonary disease overlap (ACO). We compared real-world treatment responses to biologics in ACO and asthma. Methods: We conducted a multicenter, retrospective, cohort study using data from the Precision Medicine Intervention in Severe Asthma (PRISM). ACO was defined as post-bronchodilator forced expiratory volume in 1 s (FEV1)/forced vital capacity (FVC) <0.7 and a smoking history of >10 pack-years. Physicians selected biologics (omalizumab, mepolizumab, reslizumab, benralizumab, and dupilumab) based on each United States Food & Drug Administration (FDA) approval criteria. Results: After six-month treatment with biologics, both patients with ACO (N = 13) and asthma (N = 81) showed positive responses in FEV1 (10.69 ± 17.17 vs. 11.25 ± 12.87 %, P = 0.652), Asthma Control Test score (3.33 ± 5.47 vs. 5.39 ± 5.42, P = 0.290), oral corticosteroid use (−117.50 ± 94.38 vs. −115.06 ± 456.85 mg, P = 0.688), fractional exhaled nitric oxide levels (−18.62 ± 24.68 vs. −14.66 ± 45.35 ppb, P = 0.415), sputum eosinophils (−3.40 ± 10.60 vs. −14.48 ± 24.01 %, P = 0.065), blood eosinophils (−36.47 ± 517.02 vs. −363.22 ± 1294.59, P = 0.013), and exacerbation frequency (−3.07 ± 4.42 vs. −3.19 ± 5.11, P = 0.943). The odds ratio for exacerbation and time-to-first exacerbation showed no significant difference after full adjustments, and subgroup analysis according to biologic type was also showed similar results. Conclusions: Biologics treatment response patterns in patients with ACO and asthma were comparable, suggesting that biologics should be actively considered for ACO patients as well.